Scoping Review: The Role of Personal Resilience and Personality Traits of Health Professionals In The Implementation of Interprofessional Collaboration Practice In Hospital - Yunita Gabriela Madu; Mery Solon (Department of Nursing, Faculty of Health Sciencce, Universitas Brawijaya, 2023)
Health workers have a major role in increasing public satisfaction and assessing the quality of hospital health services. To answer and get this, hospitals must pass the accreditation stage through the hospital accreditation committee, namely by having criteria for the National Hospital Accreditation Standard is Interprofessional Collaboration (IPCP) but challenges between fellow professions and from themselves because there is still autonomy from each profession. Autonomy is also a coping method health professionals use to overcome challenges. The purpose is to examine the role of personal resilience and personality traits of health professionals in IPCP implementation in hospitals. A scoping review was conducted according to PRISMA guidelines for a scoping review. The study was performed on six databases (PubMed, Clinical Key, ProQuest, EBSCO, Scopus, and Science Direct) for relevant papers published between 2017 and 2021. Search terms included